Enhanced functional response of high temperature stabilized (1-x)PMN-xPT ceramics. Issue 12 (15th August 2017) - Augustine, Pius; Rath, Martando; Ramachandra Rao, M.S.
Abstract: Synthesis of single phase (1-x)Pb(Mg1/3 Nb2/3 )O3 -xPbTiO3 ceramics with enhanced electrical response was achieved by excluding excess PbO from the precursor, making them suitable for device applications. This report is an inquiry into the effect of high temperature stabilization used for the realization of single phase PMN-PT ceramics on the electrical properties exhibited by the compositions in the morphotropic phase boundary. Functional response exhibited by the high temperature stabilized ceramics is correlated with the structural fluctuations in the morphotropic phase boundary and the grain pattern observed in the microstructure. Gradual transition from diffuse relaxor ferroelectric system to normal ferroelectric system was also studied. Enhanced ferroelectric response of the composition x=0.35 (Psat =32.03  μC/cm 2, Pr =25.11  μC/cm 2, EC =6.04  kV/cm, Rsq =1.28, Absolute area=3768, range of electric field=−37 to +37  kV/cm and recoverable energy density=59.86 mJ/cm 3 ), the improved dielectric behavior of the composition x=0.325 (εr(max) =15, 703, Tanδmax =0.02 and γ=1.79 (at 1 kHz)) and the high piezoelectric coefficient d 33 (390 pC/N and365 pC/N for x=0.325 and x=0.35 respectively), obtained in the study have confirmed the device worthiness of the synthesized ceramic compositions. This study was carried out to establish that, modulated high temperature synthesis will not deteriorate the electrical properties of the lead based system like PMN-PT, rather will assist the completion of perovskite phase formation, and thus enhance the functional response of the ceramic.